2002
DOI: 10.1124/mol.61.3.554
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester and Curcumin: A Novel Class of Heme Oxygenase-1 Inducers

Abstract: Heme oxygenase-1 (HO-1) is a redox-sensitive inducible protein that provides efficient cytoprotection against oxidative stress. Curcumin, a polyphenolic natural compound that possesses anti-tumor and anti-inflammatory properties, has been reported recently to induce potently HO-1 expression in vascular endothelial cells (Free Rad Biol Med 28:1303-1312. Here, we extend our previous findings by showing that caffeic acid phenethyl ester (CAPE), another plant-derived phenolic agent, markedly increases heme oxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
214
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(232 citation statements)
references
References 40 publications
14
214
2
2
Order By: Relevance
“…Rosmarinic acid, resveratrol and o-and p-coumaric acids (5-100 mM L À1 ) were not able to activate the HO-1 enzyme; on the contrary, some of the mentioned compounds decreased HO-1 activity at the concentrations tested. Unlike them, ethyl ferulate, when applied at low (15 and 5 mM L À1 ), but not high, concentrations effectively induced HO-1 activity and mRNA expression in astrocytes as well as protein expression in astrocytes (in cell cultures) after 6 h of incubation (70).…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Rosmarinic acid, resveratrol and o-and p-coumaric acids (5-100 mM L À1 ) were not able to activate the HO-1 enzyme; on the contrary, some of the mentioned compounds decreased HO-1 activity at the concentrations tested. Unlike them, ethyl ferulate, when applied at low (15 and 5 mM L À1 ), but not high, concentrations effectively induced HO-1 activity and mRNA expression in astrocytes as well as protein expression in astrocytes (in cell cultures) after 6 h of incubation (70).…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 90%
“…Scapagnini et al (70), for instance, showed that caffeic acid phenethyl ester significantly increased the expression of heme oxygenase-1 (HO-1) in astrocytes in cell cultures at low (15-50 mM L À1 ) but not at high concentrations (up to 100 mM L À1 ). The induction of the enzyme was accompanied by an early increase in the levels of reduced gluthatione followed by an elevation in the content of the oxidized form of gluthatione.…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 99%
“…It has been reported that curcumin protects endothelial cells against oxidative injury (Motterlini et al, 2000;Scapagnini et al, 2002;Foresti et al, 2005). We therefore examined whether DMC and BDMC could also be cytoprotective against oxidative injury in endothelial cells.…”
Section: Effects Of Curcuminoids On Endothelial Cell Injury Caused Bymentioning
confidence: 96%
“…Previous studies have shown that endothelial HO-1 provides cytoprotection against oxidative injury (Motterlini et al, 2000;Scapagnini et al, 2002;Foresti et al, 2005). Thus, we tested whether curcuminoid-induced HO-1 expression could facilitate cytoprotective effect.…”
Section: Role Of Endothelial Ho-1 In Curcuminoid-induced Cytoprotectionmentioning
confidence: 99%
See 1 more Smart Citation